Temperament and Social Hierarchy in a Colony of Juvenile Male Southern Pig-Tailed Macaques (Macaca nemestrina) at the Primate Research Center, IPB University (Indonesian Journal of Primatology, 2026)
The use of southern pig-tailed macaques (Macaca nemestrina) as animal models requires adherence to animal welfare principles and the 3Rs (replacement, reduction, and refinement). This study aimed to characterize the temperament of individual juvenile pig-tailed macaques and to determine the social hierarchy structure within a captive colony to support the development of appropriate management and training strategies. Temperament assesssment was conducted through behavioral observations using a standardized ethogram durig 20-minute focal samping sessions, four sessions per day over 14 consecutive days. The subjects were four juvenile males aged approximately three years housed in colony cage GM 2/4 at the Research Animal Faciity at Lodaya (RAF-L), Primate Research Center, IPB University. We recorded 2,838 behavioral events across five temperament categories (aggresive, neutral, affiliative, submissive, and anxious). A one-way ANOVA with Tukey HSD post hoc test  revealed that affiliative behaviors were significantly more frequent than othercategories (p